Trends in Resource Utilization by Children with Neurological Impairment in the United States Inpatient Health Care System: A Repeat Cross-Sectional Study - Berry, Jay G. (Public Library of Science, 2012)
BACKGROUND: Care advances in the United States (US) have led to improved survival of children with neurological impairment (NI). Children with NI may account for an increasing proportion of hospital resources. However, this assumption has not been tested at a national level. METHODS AND FINDINGS: We conducted a study of 25,747,016 US hospitalizations of children recorded in the Kids' Inpatient Database (years 1997, 2000, 2003, and 2006). Children with NI were identified with International Classification of Diseases, 9th Revision, Clinical Modification diagnoses resulting in functional and/or intellectual impairment. We assessed trends in inpatient resource utilization for children with NI with a Mantel-Haenszel chi-square test using all 4 y of data combined. Across the 4 y combined, children with NI accounted for 5.2% (1,338,590) of all hospitalizations. Epilepsy (52.2% [n = 538,978]) and cerebral palsy (15.9% [n = 164,665]) were the most prevalent NI diagnoses. The proportion of hospitalizations attributable to children with NI did not change significantly (p = 0.32) over time. In 2006, children with NI accounted for 5.3% (n = 345,621) of all hospitalizations, 13.9% (n = 3.4 million) of bed days, and 21.6% (US$17.7 billion) of all hospital charges within all hospitals. Over time, the proportion of hospitalizations attributable to children with NI decreased within non-children's hospitals (3.0% [n = 146,324] in 1997 to 2.5% [n = 113,097] in 2006, p<.001) and increased within children's hospitals (11.7% [n = 179,324] in 1997 to 13.5% [n = 209,708] in 2006, p<0.001). In 2006, children with NI accounted for 24.7% (2.1 million) of bed days and 29.0% (US$12.0 billion) of hospital charges within children's hospitals. CONCLUSIONS: Children with NI account for a substantial proportion of inpatient resources utilized in the US. Their impact is growing within children's hospitals. We must ensure that the current health care system is staffed, educated, and equipped to serve this growing segment of vulnerable children. Please see later in the article for the Editors' Summary